The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4236/msa.2011.211211
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pigmental Properties of Nickel Phosphates by the Substitution with Tetravalent Cerium Cation

Abstract: In this paper, we report the preparation of nickel phosphate in aqueous solution and its use as inorganic pigment. Because cerium phosphate is insoluble in acidic and basic solution, the addition of cerium was tried to improve the acid and base resistance of nickel phosphate pigment. The cerium substituted nickel phosphates were prepared from phosphoric acid, nickel nitrate, and ammonium cerium nitrate solution. The additional effects of tetravalent cerium cation were studied on the chemical composition, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Thermogravimetric analysis (TGA) and differential thermogravimetric analysis (DTA) were performed in the temperature range of 25–750 °C to determine the hydration numbers of CPO and NPO. Only endothermic events (dehydration of adsorbed water and water of crystallization) were observed for CPO (Figure S2), whereas NPO exhibited a broad exothermic peak at 400 °C likely to be caused by the condensation of NiHPO 4 to Ni 2 P 2 O 7 with some dehydration . XRD measurements indicated that both CPO and NPO remained amorphous after the TGA measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Thermogravimetric analysis (TGA) and differential thermogravimetric analysis (DTA) were performed in the temperature range of 25–750 °C to determine the hydration numbers of CPO and NPO. Only endothermic events (dehydration of adsorbed water and water of crystallization) were observed for CPO (Figure S2), whereas NPO exhibited a broad exothermic peak at 400 °C likely to be caused by the condensation of NiHPO 4 to Ni 2 P 2 O 7 with some dehydration . XRD measurements indicated that both CPO and NPO remained amorphous after the TGA measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Transition metal phosphates have a weak point to solve in acidic and basic solutions. In previous work [14], the substitution with rare earth cation inhibited the elution of phosphates. Therefore, rare earth substituted iron phosphates have a possibility to use as a catalyst in solutions.…”
Section: Introductionmentioning
confidence: 85%
“…In previous work [13], the substitution with rare earth cation inhibited the elution of phosphates. Therefore, rare-earth-substituted iron phosphates have a possibility to use as a catalyst in solutions.…”
Section: Introductionmentioning
confidence: 85%